3D stochastic replicas of porous solids: a way to improve predicted diffusivity - Hejtmánek, Vladimír; Čapek, Pavel; Brabec, Libor; Zikánová, Arlette; Kočiřík, Milan; Bernauer, Bohumil (Diffusion Fundamentals, 2009)
The goal of our contribution was to develop a method providing morphological (microstructural) descriptors whose values would match total porosity and specific surface obtained other independent methods. The model obtained from limited amount of statistical information, accessible by image analysis of cross-sections, offers an attractive way for the prediction of equilibrium and transport phenomena in natural and man-made macroporous media.